'Almost everything we do includes inquiry': fostering inquiry-based teaching and learning with preschool teachers. Issue 1 (2nd January 2017) - Hollingsworth, Heidi L.; Vandermaas-Peeler, Maureen
ABSTRACT: Given the increased emphasis on science in early learning standards, two studies were conducted to investigate preschool teachers' efficacy for teaching science and their inquiry-based teaching practices. Fifty-one teachers completed a survey of their efficacy for teaching science and understanding of inquiry methods. Teachers reported moderate confidence in their abilities, but only 25% of respondents indicated knowledge of most steps of the inquiry process. In a follow-up study, a small group of teachers participated in training sessions followed by in-depth interviews. Most teachers reported implementing the beginning steps of inquiry, such as observing and questioning, within an activity, but rarely reported next steps, such as making predictions and evaluating evidence. Participants identified lack of materials, scheduling, and time constraints as challenges to inquiry-based teaching. Findings highlight the need for professional development, emphasising the integrated, sequential, cyclic nature of the inquiry process to support preschoolers' complex thinking and reasoning.